Report on the experiences of fourth year nursing students registered for the degree of bachelor of nursing science at the university of Namibia, regarding rural placement in 2014 - Kloppers, Joan.M; Nelumbu, Lucia.N; Tibinyane, Maria.B (International Journal of Medicine, 2017)
The School of Nursing and Public Health sends every year the final year nursing degree students to rural placements. Students are send to the different clinics and hospitals in regions namely; - Khomas, Otjozondjupa, Kharas, Erongo, Omaheke, Kavango East and West, Otjikoto and Zambezi region. The students were placed from the 2nd June to 4th June 2014. Rural placement is organized because of complaints received from the public sector. It was uttered that newly qualified professional nurses after having obtained their degrees, lack the skills to operate independently.Aim: The aim of rural placement for fourth year nursing students is to gain knowledge and to develop the necessary skills to practice independently under the supervision of a qualified and experience registered nurse.Method: No actual research was conducted. The answers were collected from the fourth year nursing students’ reports.Results: The findings from the report of the fourth year nursing students were positive and negative. The findings were divided in themes and sub themes by using Tech’s method. The positive responses were:Management of administrative aspects. Platform to work independently; Students learn to apply their critical thinking.Practice how to manage a health facility: Learn more on integrated management of neonatal and childhood diseasesManagement of hypertension, asthma and other emergency cases.Students Experience the difference between rural and urban. Distances were very far; roads are difficult to travel; There is not always a doctor and you had to make own decisions for the patient.Prepare students to become responsible and accountable professional nurses.Work under supervision of the registered nurse.Negative responses were: Staff shortage; no delegation at some places; poor communication; language barriers; far distances.Conclusion: Although there were some hiccups the students were very grateful for the exposure to the rural placement. Students have learnt a lot of activities they were previously not fully confident of.